PENGARUH BIAYA PEMASARAN TERHADAP HASIL PENJUALAN FOLDING GATE DAN ROLLING DOOR MFG PADA PT PUTRA AGUNG SANTOSO - Bowo Lestono (Universitas Muhammadiyah Kalimantan Timur, 2018)
Background in this research is the production as well as in marketing experience of increase or decrease, but nevertheless company can’t know for sure whether sales volume of Folding Gate and Rolling Door Mfg at PT. Son Agung Santoso in Samarinda is as a positive result of marketing expenditure activities performed or not. The formulation of the problem in this research is: